Public law, private practice : politics, profit, and the legal profession in nineteenth-century Japan - Flaherty, Darryl E., 1967- (Harvard East Asian monographs, 2013)
"Traces the transition of law regimes from Edo to Meiji, showing how the legal profession emerged as a force for change in modern Japan and highlights its lasting contributions in founding private universities, political parties, and a national association of lawyers that contributed to legal reform during the twentieth century"--Provided by publisher